2021
DOI: 10.3390/ijms22147727
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir and Its Hemocompatible More Lipophilic Derivative Can Enhance the Apoptotic Effects of Methotrexate by Inhibiting Breast Cancer Resistance Protein (BCRP)

Abstract: Efflux transporters, namely ATP-binding cassette (ABC), are one of the primary reasons for cancer chemoresistance and the clinical failure of chemotherapy. Ganciclovir (GCV) is an antiviral agent used in herpes simplex virus thymidine kinase (HSV-TK) gene therapy. In this therapy, HSV-TK gene is delivered together with GCV into cancer cells to activate the phosphorylation process of GCV to active GCV-triphosphate, a DNA polymerase inhibitor. However, GCV interacts with efflux transporters that are responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Cellular uptake of synthetic neurosteroids 1 – 11 (syntheses have been reported in our earlier publications [ 32 , 33 ]) was evaluated by using the MCF-7 (human breast adenocarcinoma; Michigan Cancer Foundation-7) cell line, which is known to express several OATPs and efflux transporters [ 34 , 35 ]. More detailed transport mechanisms were investigated by performing Eadie-Hofstee plot analysis, which revealed that almost all synthesized neurosteroids 1–11 had two distinct transport mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular uptake of synthetic neurosteroids 1 – 11 (syntheses have been reported in our earlier publications [ 32 , 33 ]) was evaluated by using the MCF-7 (human breast adenocarcinoma; Michigan Cancer Foundation-7) cell line, which is known to express several OATPs and efflux transporters [ 34 , 35 ]. More detailed transport mechanisms were investigated by performing Eadie-Hofstee plot analysis, which revealed that almost all synthesized neurosteroids 1–11 had two distinct transport mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute expressions of SNATs were quantified from the plasma membrane fractions of MCF-7 cells by LC–MS/MS method following a multiplexed multiple reaction monitoring (MRM) analysis mode according to the protocol described earlier with minor modifications. The plasma membrane fractions were isolated from three distinct sets of cell culture plates (biological replicates) by using a Membrane Protein Extraction Kit (BioVision Incorporated, Milpitas, CA, USA) according to the manufacturer’s instructions. The protein content for each fraction was measured using a Pierce BCA Protein Assay Kit (Thermo Fisher Scientific, Inc., Waltham, MA, USA), and a total amount of 50 μg proteins from each fraction was denatured, reduced, and alkylated.…”
Section: Materials and Methodsmentioning
confidence: 99%